Moderasi Beragama sebagai Upaya Preventif terhadap Tindakan Terorisme - Triono, Teguh Imam; Rahayu, Sucik; Wangsanata, Susana Aditiya; Jamalullael, Jaiz (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
The urgency of religious moderation in the context of Indonesia’s diversity is increasingly critical amid the growing potential for conflicts rooted in differences of belief. Islamic Religious Education (PAI) holds a strategic role as a medium for instilling moderation values that emphasize tolerance, balance, and rejection of violence. Conversely, radicalism and terrorism remain real threats to religion-based education when extreme religious ideologies infiltrate learning spaces. This study aims to analyze the implementation of religious moderation in educational settings, particularly in PAI learning, and to identify challenges and opportunities in strengthening such values. The research employed a descriptive qualitative method with a library research approach, involving data reduction, categorization, and synthesis of relevant literature. The analysis reveals that the integration of religious moderation has been realized through contextual learning approaches, cross-viewpoint dialogue, and reinforcement of moral education, although challenges persist in the form of limited teacher understanding, less adaptive curricula, and the negative influence of social media. The contribution of PAI lies in its capacity to build students’ critical awareness, instill the understanding of Islam as rahmatan lil-‘alamin, and strengthen the younger generation’s ideological resilience against radical ideas. The study concludes that strengthening religious moderation in PAI is an effective preventive strategy to counter radicalization and terrorism in a pluralistic Indonesia.Keywords - Deradicalization, Islamic Religious Education, Prevention, Religious Moderation, Terrorism.